Accelerated Electrosynthesis Development Enabled by High-Throughput Experimentation - Chen, Huijie; Mo, Yiming (Synthesis, 2023)
Electrochemical synthesis has recently emerged as an environmentally benign method for synthesizing value-added fine chemicals. Its unique reactivity has attracted significant interests of synthetic chemists to develop new redox chemistries. However, compared to conventional chemistry, the increased complexity caused by electrode materials, supporting electrolytes, and setup configurations create obstacles for efficient reaction discovery and optimization. The recent increasing adoption of high-throughput experimentation (HTE) in synthetic chemistry significantly expedites the synthesis development. Considering the potential of implementing HTE in electrosynthesis to tackle the challenges of increased parameter space, this short review aims at providing recent advances in the HTE technology for electrosynthesis, including electrocatalysts screening, device miniaturization, electroanalytical methods, artificial intelligence, and system integration. The discussed contents also cover some topics in HTE electrochemistry for areas other than synthetic chemistry, hoping to spark some inspirations for readers to use interdisciplinary techniques to solve challenges in synthetic electrochemistry.1 Introduction2 Parallelized Reaction Screening3 High-Throughput Screening for Electrocatalysts4 Miniaturization of Screening Devices5 Analytical Methods for Electrosynthesis Screening6 Artificial Intelligence for High-Throughput Screening7 Integrated Screening Systems8 Conclusion and Outlook
Keywords: high-throughput screening; electrochemistry; artificial intelligence; automation; device miniaturization